Alfa Generation in ELT: Teachers’ Perspective - Asni, Yulie; Tsuraya, Annisa Shofa (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
This research intends to find out the teachers’ perspectives in ELT towards the Alpha generation. It applied a qualitative approach that involved three English Teachers from three different schools in Wajo Regency. To gain the data, those participants were interviewed and its results were descriptively analyzed through four steps, namely selecting relevant data, transcribing, interpreting and reporting. The result shows that teachers are ready enough to teach the Alpha Generation related to English learning. There are some difficulties faced by teachers in the teaching process regarding the students’ behaviour differences as the result of generation characteristics. Even it is difficult, the teachers are ready and have already equipped with the ability to face changing in teaching process, included the generation switching.